Hāoẏā 49, Anilera chabi-ān̐kā āra rājanaitika bhābanā : adhunāntikera āreka elākā - Rāẏacaudhurī, Samīra, 1933-; Murśida, E. Ema; Pradhāna, Arabinda; Kumāra, Kāñcana (Hāoẏā 49 : Prāptisthāna, Pātirāma, 2004)
Contributed articles on the life and work of Anila Karañjāi, 1940-2001, painter from India.